“Chocolate” Gold Nanoparticles—One Pot Synthesis and Biocompatibility - Neelika Roy Chowdhury; Allison J. Cowin; Peter Zilm; Krasimir Vasilev (Nanomaterials, 2018)
The chemical synthesis of nanoparticles can involve and generate toxic materials. Here, we present for the first time, a one pot direct route to synthesize gold nanoparticles (AuNPs) using natural cacao extract as both a reducing and stabilizing agent. The nanoparticles were characterized by UV-visible spectroscopy (UV-VIS), dynamic light scattering (DLS), and transmission electron microscopy (TEM); and have excellent biocompatibility with human primary dermal fibroblasts.